Estimating 24‐Hour Urine Sodium From Multiple Spot Urine Samples - Rhee, Moo‐Yong (J Clin Hypertens (Greenwich), 2016)
The authors developed an equation to estimate 24‐hour urine sodium (24HUNa) using the average of three spot urine (SU) samples (morning‐first, morning, and evening) from 74 individuals and validated this equation using the average of three SU samples (morning‐first, daytime, and evening) from 174 additional individuals. Compared with previously published equations using a single SU sample, the currently developed equation using the average of three SU samples showed much lower bias from measured 24HUNa (−2.9 vs >10 mmol/24 h). The intraclass and concordance correlation coefficients of the proposed equation using the average of three SU samples were 0.909 and 0.832, respectively. The limits of agreement were −64.1–58.3 mmol/24 h and approximately 100 mmol/24 h for the currently developed and previously published equations, respectively. All equations showed a tendency to overestimate or underestimate 24HUNa in a manner dependent on the level of 24HUNa but irrespective of the number of SU samples considered. Nonetheless, among the currently tested equations, our equation using the average of three SU samples provided the best estimation of 24HUNa at a population level.